A Novel Microwave Assisted Solvent-Free General Route to 2-Amino Imidazoles - Thangavel, Neelavani; Murgesh, Kandasamy (Asian Journal of Chemistry, 2016)
In an attempt to exploit the synthetic utility of microwaves in heterocyclic chemistry, 2-amino imidazoles were synthesized with various substituents at 4th and 5th positions of imidazole ring. Several aroins were also prepared by microwave irradiation using inorganic solid support and have been reacted with guanidine nitrate to give 4,5-substituted 2-amino imidazoles in very good to excellent yields.